Algebraic Proof that $\sum\limits_{i=0}^n \binom{n}{i}=2^n$

I'm well aware of the combinatorial variant of the proof, i.e. noting that each formula is a different representation for the number of subsets of a set of $n$ elements. I'm curious if there's a series of algebraic manipulations that can lead from $\sum\limits_{i=0}^n \binom{n}{i}$ to $2^n$.

-
is the proof you looking for using $(1+1)^n=2^n$? – Arjang Jan 24 '11 at 4:30
Well, no. That one I was also aware of. It's more of a curiosity if there's any direct method to go from the summation to $2^n$. – JSchlather Jan 24 '11 at 4:40
One should not think of the algebraic and combinatorial proofs as different. There is a straightforward dictionary between algebra and combinatorics in these cases (and it is given by taking generating functions). – Qiaochu Yuan Jan 24 '11 at 9:12
Zeilberger's algorithm might do it - it's a useful tool for this kind of problem in general (sum from $-\infty$ to $\infty$ of a hypergeometric with finite support). – Peter Taylor Jan 24 '11 at 9:29
@Peter Taylor: Zeilberger's algorithm produces the recurrence given in my answer. See Section 5.8 of Concrete Mathematics. – Mike Spivey Jan 24 '11 at 14:15

Here's one. Let $g(n) = \sum \limits_{i=0}^n \binom{n}{i}$. Then

$$g(n+1) - g(n) = \sum_{i=0}^{n+1} \binom{n+1}{i} - \sum_{i=0}^n \binom{n}{i} = \sum_{i=0}^{n+1} \left(\binom{n+1}{i} - \binom{n}{i}\right) = \sum_{i=0}^{n+1} \binom{n}{i-1}$$ $$= \sum_{i=0}^n \binom{n}{i} = g(n).$$ Here, we use the fact that $\binom{n}{n+1} = \binom{n}{-1} = 0$, as well as the binomial recurrence $\binom{n+1}{i} = \binom{n}{i} + \binom{n}{i-1}$.

Thus we have $g(n+1) = 2g(n)$, with $g(0) = 1$. Since $g(n)$ doubles each time $n$ is incremented by 1, we must have $$g(n) = \sum_{i=0}^n \binom{n}{i} = 2^n.$$

-
This is more or less the same proof one would do to show that $(a+b)^n$ is what it is... – Mariano Suárez-Alvarez Jan 24 '11 at 5:40
@Mariano: Good observation. In fact, see the proof of Identity 1 in this paper: math.pugetsound.edu/~mspivey/CombSum.pdf – Mike Spivey Jan 24 '11 at 5:57
Very nice and this proof seems to be analogous to what picakhu did as well. – JSchlather Jan 24 '11 at 5:57

You could use exponential generating functions to prove this identity. $$\begin{eqnarray}\sum_{n\ge0}2^n\frac{x^n}{n!}&=&\sum_{n\ge0}\frac{(2x)^n}{n!}\\&=&e^{2x}\\&=&e^xe^x\\&=&\sum_{i\ge0}\frac{x^i}{i!}\sum_{j\ge0}\frac{x^j}{j!}\\&=&\sum_{n\ge0}\sum_{i=0}^{n}\frac{x^i}{i!}\frac{x^{n-i}}{(n-i)!}\\&=&\sum_{n\ge0}\sum_{i=0}^n\binom{n}{i}\frac{x^n}{n!}\end{eqnarray}$$ Now, comparing the coefficients of $x^n$ for ${n\ge0}$ gives the identity.

-

Simply use the binomial formula.

$$(a + b)^n = \sum_{k=0}^n {n \choose k} a^k b^{n - k}$$

With $a = b = 1$ you have your result.

-

Well, here is one.

$$\sum_{i=0}^n \binom{n}{i}=2^n$$ $$\sum_{i=0}^n \binom{n}{i}+\sum_{i=0}^n \binom{n}{i}=2^{n+1}$$ $$\binom{n}{0}+\left [ \binom{n}{0}+\binom{n}{1} \right ]+...+\left [ \binom{n}{n-1}+\binom{n}{n}\right ]+\binom{n}{n}=2^{n+1}$$ $$\sum_{i=0}^{n+1} \binom{n+1}{i}=2^{n+1}$$

-
So you're using induction? And I assume that in your last step it should be $\sum_{i=0}^{n+1}\binom{n+1}{i}$? – JSchlather Jan 24 '11 at 4:41
Yup, sorry about that. – picakhu Jan 24 '11 at 4:43